Covid-19 Vaccine Surveillance in Saudi Arabia: Opportunities for Real-time Assessment - Yasser Albogami; Hadeel Alkofide; Adel Alrwisan (Elsevier, 2021)
After months of confronting COVID-19 pandemic, several countries, including Saudi Arabia, have recently approved newly developed vaccines to prevent COVID-19 infection. With the new technology utilized to develop some vaccines, questions arise about their long-term safety. To provide rapid response to emerging safety issues, robust surveillance programs that provide near real-time analysis of vaccines effects are required. Saudi Arabia has a well-established passive pharmacovigilance system that monitors drugs and vaccines safety. However, recent development in health digitalization in Saudi Arabia may provide a unique opportunity to harvest existing resources to generate high-quality evidence. This commentary provides an overview of the available systems that can be utilized to monitor the COVID-19 vaccines' safety and discusses opportunities for data integration to improve data quality and generate real-world evidence on COVID-19 vaccine safety.